EFFECTS OF LONGER OF DUTY HOURS ON WORK LIFE BALANCE OF STAFF WORKING IN DEPARTMENT OF MUMBAI POLICE - Dr. Shaji K. Joseph; Ms. Monika P. Bhosale (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The duty hours or working hours is an important variable to understand the work life balance concept. They are together dependent on each other. If one factor changes then it can get impacted on the other factor. Here, the study considered the duty are performed by police employees in the department. Long duty hours are always a challenge for the police employee while performing their duties. The researcher tried to find out the duty of hours patterns, the work life balance and its relation in the present stud. The study is undertaken on the police employees especially the police constable working in Mumbai area. Total 60 respondents from different Police stations of Mumbai. For data analysis SPSS software is used with Krushal Wallis and frequency distribution for testing of hypothesis. The study is concluded with a duty hour one of the important factors in deciding walk life balance of police. The department has to make a provision for reduction of duty hours of police employees.